Meningkatkan UMKM Melalui Pemasaran Digital (Brand Awareness) di Desa Pasireurih - Muhammad Syaghani; Habibullah Ahmad; Nurul Hidayat (Jurnal Informasi Pengabdian Masyarakat, 2025)
This article discusses the implementation of a community service program in the form of a Community Service Program (KKN) by FIKOM students of Pancasila University to increase brand awareness of MSMEs “Palapus” in Pasireurih Village, Bogor Regency. The main focus of the activity was to utilize digital marketing through the Instagram platform to increase the attractiveness of nutmeg-based products. The program involved creating a new logo, updating product catalog photos, and producing a short advertising video highlighting the health benefits of nutmeg. In addition, mentoring was provided to local youth to improve their skills in digital marketing strategies. The methods used include direct observation of the problems faced by MSMEs, digital marketing training, and collaboration with the younger generation to support product promotion management. The results of the program showed an increase in the visibility and competitiveness of “Palapus” MSME products, as well as an increase in the digital skills of local youth. Thus, this activity succeeded in having a positive impact on local economic growth and MSME business sustainability. This article emphasizes the importance of technological adaptation in digital marketing to support MSME competitiveness in the industrial era 4.0. The program also demonstrates the strategic role of the younger generation in driving innovation and community-based creative economic development.